The effect of dietary carbohydrate on genes for fatty acid synthase and inflammatory cytokines in adipose tissues from lean and obese subjects - Hudgins, Lisa C.; Baday, Aline; Hellerstein, Marc K.; Parker, Thomas S.; Levine, Daniel M.; Seidman, Cynthia E.; Neese, Richard A.; Tremaroli, Jolanta D.; Hirsch, Jules (The Journal of nutritional biochemistry, 2008)
Hepatic de novo lipogenesis (DNL) is markedly stimulated in humans by low-fat diets enriched in simple sugars. However, the dietary responsiveness of the key enzyme controlling DNL in human adipose tissue, fatty acid synthase (FAS), is uncertain. Adipose tissue mRNA for FAS is increased in lean and obese subjects when hepatic DNL is elevated by a eucaloric, low-fat, high-sugar diet. Twelve lean and seven obese volunteers were given two eucaloric diets (10% vs. 30% fat; 75% vs. 55% carbohydrate; sugar/starch 60/40) each for 2 weeks by a random-order cross-over design. FAS mRNA in abdominal and gluteal adipose tissues was compared to hepatic DNL measured in serum by isotopic and nonisotopic methods. Adipose tissue mRNA for tumor necrosis factor-α and IL-6, which are inflammatory cytokines that modulate DNL, was also assayed. The low-fat high-sugar diet induced a 4-fold increase in maximum hepatic DNL ( P<.001) but only a 1.3-fold increase in adipose tissue FAS mRNA ( P=.029) and no change in cytokine mRNA. There was a borderline significant positive correlation between changes in FAS mRNA and hepatic DNL ( P=.039). Compared to lean subjects, obese subjects had lower levels of FAS mRNA and higher levels of cytokine mRNA ( P<.001). The results suggest that key elements of human adipose tissue DNL are less responsive to dietary carbohydrate than is hepatic DNL and may be regulated by diet-independent factors. Irrespective of diet, there is reduced expression of the FAS gene and increased expression of cytokine genes in adipose tissues of obese subjects.